Thermo-mechanical debonding map for repairing composite–metal adhesive joints - Srinivasan, Dharun Vadugappatty (2021)
Adhesive bonding is one of the dominant joining technologies in Design for Assembly to obtain innovative engineering products with complex geometries. These permanently bonded joints could be disassembled for repair purposes using the thermo-mechanical debonding technique to salvage the high-cost composite components without any damage. In this work, the temperature dependent storage modulus, loss modulus and tensile properties of the bulk modified epoxy film adhesive were measured through instrumented tests. Glass fibre reinforced composite and Ti–6Al–4V alloy sheets were bonded with the modified epoxy film adhesive and the floating roller peel performance was studied as a function of temperature to understand the load-displacement and failure mechanisms for generating a debonding map. The debonding region was identified in the temperature range between 1.17 Tg and 1.33 Tg. The knock-down in storage modulus and initial peel load exhibited a similar trend with respect to the temperature.